Answer:
x+y=11
y=-x+11
Explanation:
In order to solve this we first have to find the slope of the function, remember the formula of the slope:
![Slope=(y2-y1)/(x2-x1)\\ Slope=(2-3)/(9-8)\\ Slope=(-1)/(1)\\ Slope=-1](https://img.qammunity.org/2020/formulas/mathematics/college/f1tye57yt5sllwj4anmqy1jofj4anq8zl4.png)
The slope is -1, based on this we can calculate the formula for the equation with the general function:
y-y1= M(x-x1)
y-8=-1(x-3=
y-8=-x+3
y+x-11=0
Now in the slope form you just clear y from the equation:
y=-2-x+11
So that is the answer to the question.